Implementasi Layanan Paket Hemat (PAHE) Akta Kelahiran Sebagai Inovasi Pelayanan Publik di Kelurahan Sidotopo Wetan - Adi Pangestu, Aryan; Reviandani, Oktarizka (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to find out how the Save Package (PaHe) service for making birth certificates is implemented as a public service innovation in Sidotopo Wetan Village. The Birth Certificate Savings Package (PaHe) service aims to make it easier for people to process population documents, one of which is making a birth certificate. Even though there have been these innovations, there are still many people who are late and have not processed birth certificates in accordance with existing policies. This research uses qualitative research methods to describe the phenomena that occur, where the data sources used in this research are primary data sources (interviews, field observations) and secondary data (books, journals, news, articles, etc.). The focus of this research is to see how the Birth Certificate Savings Package (PaHe) service is implemented in Sidotopo Wetan Village with indicators of communication, resources, disposition and organizational structure. Based on the research results previously explained, it can be concluded that the implementation of the Birth Certificate Savings Package (PaHe) service as one of the public service innovations in Sidotopo Wetan Subdistrict can be said to have been implemented quite well even though it has not been optimal as expected. Suggestions that can be made are to increase the number of service officers and increase public awareness regarding orderly population administration.